234. Susceptibility-weighted MRI values correlate with motor and cognitive dysfunction in Parkinson's disease. (December 2018) - Chiappiniello, A.; Tambasco, N.; Paoletti, F. Paolini; Lisetti, V.; Chiarini, P.; Nigro, P.; Simoni, S.; Brahimi, E.; Tarducci, R.; Floridi, P.; Parnetti, L.; Calabresi, P.
Abstract : Introduction: Brain iron load is an important neuropathological mark in Parkinson's disease (PD) and it can be quantified by MR susceptibility-weighted imaging (SWI). We estimated the correlation between cerebral iron distribution evaluated by SWI and cognitive pattern in a group of PD patients. Materials and methods: 32 patients and 10 healthy subjects comparable for age and gender were enrolled. Patients were examined for motor and cognitive assessment. Cognitive outline was assessed with MoCA for global cognitive abilities and with a battery of neuropsychological tests. Functional daily abilities were tested using ADL and IADL scales. Patients and controls underwent MRI acquisition on a 3.0 T Philips Achieva system. For each emisphere seven ROIs were considered: putamen, globus pallidus, caudate nucleus, red nucleus, substantia nigra, dentate nucleus and frontal white matter. We measured SWI-intensity values for each ROI: lower values correspond to higher iron content. All the collected data were expressed as mean value and standard deviation. Chi-square test was used to verify associations between categorical variables. Results: Higher iron deposits were detected in all the ROIs in patients compared to controls. SWI-intensity values of substantia nigra correlates negatively with disease duration and UPDRS-III off and positively with ADL and IADL scores. A positive and significant relationship between MoCA (<26 cut-off) and SWI-intensity values in putamen, globus pallidus and substantia nigra was found. WAIS-IV Similarities shows a significant positive association with SWI-intensity values in all the ROIs, moreover Spatial Span and Gradient Named Test positively correlate with SWI intensity values of substantia nigra. Conclusions: According to literature[1], brain iron distribution estimated by SWI seems to be a useful tool for cognitive decline in PD.